Evaluasi Pembelajaran di Madrasah Diniyah Miftachul Hikmah Denanyar Tangen Sragen - Subar Junanto (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2016)
The problems occurred in Madrasah Diniyah Miftachul Hikmah were the lack of funding, teachers’ competence, facilitiesand infrastructure, as well as theallocation of study time. The aim of this study was to evaluate the learning process at this school. This research employed combined qualitative and quantitative methods;conducted in Madrasah Diniyah Miftachul Hikmah Denanyar village, Tangen subdistrict, Sragen regency on 2015. The subject of this study was the teachers and students of this school.The data was gathered through aquestionnaire, observation, interview, and documentation which later analyzed quantitatively and qualitatively using CIPP (context, input, process, product) evaluation model. The ContextEvaluation showed that community’s participation in administrating this school was low, evidenced by the absent of suggestions and ideas from students’ parents for the continuation of the program. The Input Evaluation indicated that facilities and infrastructure in this school categorized as inadequate, only 60% of the real need of supporting facilities, learning materials, skills materials and kits are. The Process Evaluation on teachers activities in the learning process observed from preparation, strategy, ending the class, management and evaluation of learning process are categorized as adequate. Lastly, the Product Evaluation based on the data showed that majority of students thought that Madrasah Diniyahprovides enough benefits, none of them thought otherwise.Keywords: Learning evaluation, Madrasah Diniyah, CIPP evaluation model.